COVID-19 diagnosis and hospital admissions in Brazil: a countrywide survey (Covitel, 2022) - Renato Teixeira; Sofia Reinach; Fátima Marinho; Pedro Hallal; Fernando César Wehrmeister; Eduardo Ribes Kohn; Érika Carvalho de Aquino; Pedro de Paula; Luciana Monteiro Vasconcelos Sardinha (Revista Brasileira de Epidemiologia)
ABSTRACT Objective: To estimate the prevalence of COVID-19 diagnosis and hospital admissions, and to evaluate their correlates in a nationwide Brazilian sample. Methods: A cross-sectional study was carried out with secondary data from the Telephone Survey of Risk Factors for Chronic Noncommunicable Diseases in Times of Pandemic – Covitel 2022. The Covitel study uses cluster sampling, carried out through random digit dialing on landlines and cell phones, among people aged 18 years or over. The outcome of the “diagnosis of COVID-19” was based on a self-report of a confirmed case through laboratory tests or medical diagnoses. Those who reported COVID-19 were asked about the need for hospital admission due to COVID-19. Independent variables included sex, age, level of education, region, comorbidity, private health insurance plan, self-rated health, and employment status. The odds ratio was estimated using logistic regression models considering the complex sample design. Results: From the sample of 9000 people, the prevalence of COVID-19 diagnosis was 25.4% (95%CI 23.8–27.1%), ranging from 23.0% (95%CI 20.0–26.3%) in the Northeast region to 28.5% (95%CI 25.3–31.7%) in the South region. Middle-aged adults (35–44 years old) had the highest prevalence of COVID-19 diagnosis. The higher the level of education, the higher the prevalence of COVID-19 diagnosis. Conclusion: The prevalence of COVID-19 diagnosis is markedly different from that of SARS-CoV-2 infection at the population level. Socioeconomic differences in access to testing are the likely explanation. Older adults and people with comorbidities were more likely to be admitted to hospital due to COVID-19 in Brazil.